Media Informasi Dan Komunikasi Pemerintah Provinsi Jawa Barat - Renata Anisa; Rachmaniar Rachmaniar (LONTAR: Jurnal Ilmu Komunikasi, 2019)
The development of information technology in Indonesia grow rapidly, manyinstitution using digital media to communicate with the public. Internet users in Indonesia on2017 is 143.26 million. This is in line with the increase of the number of users of socialmedia.To reach a large public, Governments need to use digital media to deliver informationand communicating with the public.The purpose of the research is to describes the information and communicationmedia used by the provincial Government of West Java to communicate with the public andwhat kind of information which delivered through official media of government. This studyuses qualitative methods, with the virtual Ethnography approach by analyzing theinformation on social media and user interaction in the cyber space. Data collection processis using observation of participation.The results of the study show that the provincial Government of West Java usingofficial website, social media platform as instagram, facebook, twitter, youtube, and email tocommunicate with public. The type of information which delivered by official mediaprovincial government of west java are the policy and Government program, tourisminformation, tax, natural disasters, health, sports, the achievements of the Government,activities, and the special event. Information which delivered through official website aremore formal and presented comprehensive. Nevertheless, information delivered through allsocial media platform is the same information, in a different format